Implikasi Teologi Praktis Jemaat Mula-Mula Yerusalem bagi Kehidupan GPdI Eben Haezer Antutan - Mokodaser, Frits; Triposa, Reni; Boiliu, Esti Regina (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2025)
This study discusses the life of the early church as recorded in Acts 2:42-47, which explains the practical theological standards for the church today, especially for the life of the GPdI Eben Haezer church in Antutan village. Referring to the early church in Jerusalem, we can see that the early church was full of faithfulness in teaching and deepening the word of God, close fellowship, and prayer as a way of life, as well as a very high and tangible level of social concern. This pattern of life not only reflects unity in a community centred on Christ, the head of the church, and illustrates the fullness of the Holy Spirit, but it also illustrates a balanced life between our relationship with God and our relationships with other human beings. This study uses a qualitative approach with a literature study method. The conclusion of this study reveals that emulating the life of the early church in Jerusalem will strengthen the church today, especially the GpdI Eben Haezer congregation in Antutan village, to become a church community that is faithful to the word of God, filled with the power of the Holy Spirit, and become a practical guide in faith development, fellowship, and ministry amid economic challenges and globalisation.AbstrakPenelitian ini membahas mengenai kehidupan yang ada di jemaat mula-mula seperti yang sudah tercatat di dalam Kisah Para Rasul 2:42-47 dimana di jelaskan mengenai standar teologis praktis bagi gereja saat ini khusunya bagi kehidupan di gereja GPdI Eben Haezer desa Antutan. Jika merujuk kepada jemaat mula-mula di Yerusalem maka bisa mengetahui bahwa jemaat mula-mula penuh dengan kesetiaan dalam pengajaran dan pendalam firman Tuhan, persekutuan yang erat, dan doa sebagai gaya hidup, serta kepedulian sosial yang sangat tinggi dan nyata. Pola kehidupan ini bukan hanya mencerminkan persatuan dalam komunitas yang berpusat kepada sang kepada gereja yaitu Kristus dan menggambarkan kepenuhan Roh Kudus, namun hal ini juga menggambarkan kehidupan yang seimbang antara hubungan dengan Allah dan hubungan antara umat manusia. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi literatur Kesimpulan penelitian ini mengungkapkan bahwa meneladani kehidupan jemaat mula-mula di Yerusalem maka akan memperkuat gereja saat ini khususnya jemaat GpdI Eben Haezer desa Antutan agar menjadi komunitas gereja yang setia kepada firman Tuhan, di penuhi noleh kuasa karya Roh Kudus serta menjadi pedoman pratis dalam pembinaan iman, persekutuan, dan pelayanan di tengah tantangan ekonomi dan globalisasi.